Inflammasome activation and formation of ASC specks in patients with juvenile idiopathic arthritis - Wittmann, Nico; Mishra, Neha; Gramenz, Jana; Kuthning, Daniela; Behrendt, Ann-Kathrin; Bossaller, Lukas; Meyer-Bahlburg, Almut (Frontiers in Medicine, 2023)
Objective The formation of large intracellular protein aggregates of the inflammasome adaptor ASC is a hallmark of inflammasome activation and characteristic of autoinflammation. Inflammasome activated cells release the highly proinflammatory cytokine IL-1β in addition to ASC specks into the extracellular space. Autoinflammatory activity has been demonstrated in systemic JIA, however minimal data exist on the role of inflammasomes in other JIA subtypes. We therefore investigated, if pyroptotic cells are present in the circulation of oligo- and poly-articular JIA. Methods Peripheral blood of JIA patients (n = 46) was investigated for ASC speck formation, a key step in inflammasome activation, by flow cytometry and immunofluorescence. Free ASC and proinflammatory cytokine levels were determined by ELISA and multiplex assay. Results Oligo-articular JIA patients showed a significantly increased proportion of ASC speck+ monocytes compared to poly-articular JIA patients. In serum free ASC alone is not sufficient to assess inflammasome activity and does not correlate with ASC speck+ monocytes. Compared to control several cytokines were significantly elevated in samples of JIA patients. JIA serum containing antinuclear antibodies, incubated with ASC specks boosts a secondary inflammation by IL-1β production in macrophages. Conclusion For the first time, we detect ex vivo inflammasome activation by ASC speck formation in oligo- and poly-articular JIA patients. Most notably, inflammasome activation was significantly higher in oligo- compared to poly-articular JIA patients. This data suggests that inflammasome derived autoinflammation may have a greater influence in the previously thought autoimmune oligo-articular JIA patients.